Shape-stabilized low melting-point alloy/expanded graphite composite thermal pad with excellent chip heat dissipation performance. (25th November 2022) - Zhao, Yu; Zhang, Zhengguo; Ling, Ziye; Gao, Xuenong; Fang, Xiaoming
Highlights: A low melting point alloy/expanded graphite composite thermal pad is prepared. The oxidation of the alloy is beneficial to its adsorption by expanded graphite. The composite thermal pad possesses a high thermal conductivity of 26.94 W/m·K. A very low thermal impedance of 0.42 K·cm 2 /W is achieved by the thermal pad. The thermal pad shows higher heat dissipation efficiency than the commercial one. Abstract: Thermal interface materials that possess high thermal conductivity and can reach low thermal impedance during service, are highly desirable for chip heat dissipation systems, especially when cooling high-power chips. Herein, a novel thermal pad was developed by combining low melting point alloy having metal-level thermal conductivity and liquid-like rheological property with expanded graphite possessing large pore volume and high thermal conductivity. Specifically, the alloy 62.5Ga21.5In16Sn was modified by the trace-oxidation method to obtain oxidized alloy, followed by adsorbing into expanded graphite and then molding and pressing to fabricate the thermal pad. It is found that the oxidation treatment resulted in the generation of refractory metal oxides Ga2 O3 and SnO2 within the alloy, thereby preventing the leakage of the alloy from the composite thermal pad. Impressively, the optimal low melting point alloy/expanded graphite composite thermal pad, prepared at the oxidation duration of 24 min, expanded graphite mass fraction of 4 % and compact density of 3.125 g/cm 3, reached a thermal conductivity of as high as 26.94 W/m·K and a thermal impedance of as low as 0.42 K·cm 2 /W, along with exhibiting a good shape-stability. More significantly, when employed into a simulative desktop CPU cooling system, this thermal pad exhibited 36.78 % higher cooling efficiency under the forced air convection, extended ten times in the time for the chip to reach the upper limit temperature (100 ℃) under the natural air cooling, and benefited to the chip to fight with the pulse-type instantaneous thermal shock, as compared to the commercial thermal pad. These excellent characteristics and good heat dissipation performance make the low melting point alloy/expanded graphite composite thermal pad show great potential for use in chip thermal management systems.